APPLICATION OF A NUMERICAL WAVE CHANNEL TO STUDY WAVES AND SEAWALL INTERACTION - Hieu, Phung Dang; Vinh, Phan Ngoc; Tai, Nguyen Van; Toan, Du Van; Duoc, Nguyen Tan; Hung, Nguyen Thanh (Vietnam Journal of Marine Science and Technology, 2014)
This paper presents the results of numerical experiments of waves and a combined seawall interaction using a numerical wave channel. Firsly, the concept of numerical wave channel and the foudation for buiding a numerical wave channel is presented. Then, the experimental conditions for both numerical experiment and laboratory one are described. The results of the laboratory and numerical experiments were analyzed and compared in order to ensure the validity of the numerical simulation and give a confidence in further detail analyses of numerical results on waves and the seawall interaction. The research results showed that the numerical wave channel had good capability in conducting numerical experiments with high nonlinearity of waves including the wave breaking and wave overtopping processes. The comparison results between laboratory data and numerical results showed satisfactory agreements. The sesults also revealed that the structure of currents under wave motion was very complicated, especially in the area surrouding the breaking point. The laboratory results showed that the wave overtopping was very nonlinear and different among the laboratory experiments although these experiments were done in thesame experimental condition.